Comparative histomorphometrical study of genital tract in adult laying hen and duck - Ahmad-Ali Mohammadpour; Abdolkarim Zamanimoghadam; Massoumeh Heidari (Veterinary Research Forum, 2012)
This study was carried out to compare the histomorphological structures of oviductal regionsof the apparently healthy adult laying hens (Gallus gallus dometicus) and ducks (Ansa ansadomesticus). For this purpose, 20 hens and 20 female ducks aged between 1–1.5 years were used. After euthanasia, the oviducts were dissected out and all of the gross morphometrical parameters including length, width and thickness as well as weight and length of them were recorded. For histological studies, after tissue preparation and staining with H&E, histological layers of isthmus, uterus and vagina were recognized and the size of them with micrometry method were determined. Our data analyses indicated that, the mean weight, length of oviduct as well as weight of isthmus, uterus in hen were significantly (P < 0.05) greater than that of duck, whereas the vaginal thickness and weight were greater in duck than the hen. In histological studies, epithelium and cilia were well developed in duck and lamina propria was filled with glands in the regions of the isthmus and uterus. The length of primary mucosal folds of isthmus and uterus in duck was more than hen. The longest mucosal fold has been seen in uterus. Most of the parameters in duck were greater than hen except the length of secondary fold of three parts of oviduct including isthmus, uterus, and vagina.